COUNTERING POLICIES AND INTERVENTIONS STUNTING IN INDONESIA - Insan, Nur (Preventif Journal, 2024)
ABSTRACT Indonesia's stunting prevalence rate in 2021 is 24.4%, classified as high compared to the world stunting prevalence rate in the same year. The government has made various efforts to overcome the stunting problem that occurs through policies and interventions. This article aims to provide an explanation of stunting prevention policies and interventions in Indonesia. The method used in this research is the literature study method through collecting library data, reading and taking notes, and managing research materials. The research results show that there are various stunting prevention programs which are a synergy between ministries and institutions. There are two intervention models in overcoming stunting, namely specific nutrition interventions and sensitive nutrition interventions. Specific nutritional interventions focus on fulfilling the nutrition of priority target groups, namely pregnant women, breastfeeding mothers, children aged 0-23 months, teenagers and women of childbearing age and children aged 24-59 months. Sensitive nutrition interventions focus on improving the provision of drinking water and sanitation, increasing access and quality of nutrition and health services, increasing awareness, commitment and practices for maternal and child care and nutrition as well as increasing access to nutritious food. The accumulation of stunting prevention policy and intervention programs has succeeded in reducing Indonesia's stunting prevalence rate to 21.6% in 2022. This can be a reference for reducing Indonesia's stunting prevalence rate to 14% in 2024 in accordance with the RPJMN target. Keywords: intervention, policy, stunting